2015
DOI: 10.7717/peerj.1409
|View full text |Cite
|
Sign up to set email alerts
|

Variation in partner benefits in a shrimp—sea anemone symbiosis

Abstract: Symbiotic interactions, where two species occur in close physical proximity for the majority of the participants’ lifespans, may constrain the fitness of one or both of the participants. Host choice could result in lineage divergence in symbionts if fitness benefits vary across the interaction with hosts. Symbiotic interactions are common in the marine environment, particularly in the most diverse marine ecosystems: coral reefs. However, the variation in symbiotic interactions that may drive diversification is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…A study on Periclimenes yucatanicus (Ives, 1891) collected from two morphologically different sea anemone hosts (Stichodactyla helianthus (Ellis, 1768) and Bartholomea annulata (Le Sueur, 1817)) found that larger sized hosts were capable of supporting larger and more fecund shrimp irrespective of the host species (McKeon & O Donnell, 2015). The authors suggested that host preference might be determined by host size, via its effect on fecundity in P. yucatanicus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study on Periclimenes yucatanicus (Ives, 1891) collected from two morphologically different sea anemone hosts (Stichodactyla helianthus (Ellis, 1768) and Bartholomea annulata (Le Sueur, 1817)) found that larger sized hosts were capable of supporting larger and more fecund shrimp irrespective of the host species (McKeon & O Donnell, 2015). The authors suggested that host preference might be determined by host size, via its effect on fecundity in P. yucatanicus.…”
Section: Discussionmentioning
confidence: 99%
“…This level of detail is also available for two free-living species of a body size similar to the majority of symbiotic species, Cuapetes americanus (Kingsley, 1878) (Negri et al, 2017) and Phycomenes siankaanensis (Martinez-Mayén & Román-Contreras, 2006) (Martínez-Mayén & Román-Contreras, 2009, as Periclimenes siankaanensis). More information is available on the number of eggs produced in symbiotic Palaemonidae, with this being available for several sea-anemone symbionts (Omori et al, 1994;McKeon & O Donnell, 2015), a fishcleaner also inhabiting sea-anemones (Spotte, 1999), a gorgonian associate (Heard & Spotte, 1991), bivalve associates (Johnson & Liang, 1966;Corey & Reid, 1991;Bruce, 2000), as well as several free-living species (Corey & Reid, 1991) of similar body size to the symbiotic species. All these studies have, however, only concentrated on a single species, with no sympatric or host-sharing taxa documented, in contrast to studies in other families (Soledade et al, 2017).…”
Section: Introductionmentioning
confidence: 99%